How can GeoGebra support physics education in upper-secondary school—a review. (17th June 2021) - Solvang, Lorena; Haglund, Jesper
Abstract: Recently, GeoGebra, a mathematics education software, has entered the scene of physics education; however, research on how the software can be used to support teaching and learning physics is limited and scattered. The aim of this article is to present a review of the current literature on how GeoGebra can be used to support physics education in upper-secondary schools. The general conclusion that comes from these studies is that GeoGebra is a user-friendly software that can be operated intuitively by teachers and students. It provides an environment in which the underlying mathematical structures are always at hand, enabling users to see connections between physical phenomena and their formal representations. In addition, teachers with or without programming skills can use the software to design custom-made computer simulations and augment real experiments with virtual objects. Our intention is to help teachers who would like to start using GeoGebra or to broaden the use of the software in physics education.